2010
DOI: 10.1007/s00436-010-2030-8
|View full text |Cite
|
Sign up to set email alerts
|

Theileria parva genetic diversity and haemoparasite prevalence in cattle and wildlife in and around Lake Mburo National Park in Uganda

Abstract: Wildlife, especially Cape buffalo (Syncerus caffer), are thought to act as a reservoir for many of the important tick-borne pathogens of cattle. In this study, we have determined the prevalence of the most significant tick-borne haemoparasites in wildlife (buffalo, impala, eland and bushbuck) as well as in cattle grazing inside and neighbouring Lake Mburo National Park (LMNP) in Uganda. A high percentage of buffalo were carriers of Theileria parva, Theileria mutans, Theileria velifera, Theileria buffeli and Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 19 publications
(25 reference statements)
2
47
1
Order By: Relevance
“…Thus the published data suggest that infections with these parasite species are rare but whether this is due to inherent resistance is not clear. Previous data (Oura et al, 2010) from cattle grazing in or near LMNP which are also not infected with E. ruminantium, B. bovis or B. bigemina, despite being susceptible to these pathogens, supports the view that these pathogens are not present rather than their absence from buffalo reflecting inherent resistance.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Thus the published data suggest that infections with these parasite species are rare but whether this is due to inherent resistance is not clear. Previous data (Oura et al, 2010) from cattle grazing in or near LMNP which are also not infected with E. ruminantium, B. bovis or B. bigemina, despite being susceptible to these pathogens, supports the view that these pathogens are not present rather than their absence from buffalo reflecting inherent resistance.…”
Section: Discussionmentioning
confidence: 63%
“…taurotragi, which is considered to be primarily a parasite of eland (Grootenhuis et al, 1980), was not present in any of the sampled buffalo, suggesting that buffalo are resistant to this parasite. Eland are present in all the sampled parks except QENP and, in a recent study of animals from LMNP (Oura et al, 2010), 100% of the eland were infected with T. taurotragi. Additionally, a previous study showed that T. taurotragi was present in a significant percentage of cattle in Uganda (Oura et al, 2004b) leading to the conclusion that the parasite was likely to be circulating directly amongst cattle populations in that country.…”
Section: Discussionmentioning
confidence: 97%
“…Of interest, is that RLB screening of Nyala, Eland and Kudu also did not detect T. velifera in areas endemic for A. hebraeum and A. variegatum (Oura et al 2011;Pfitzer et al 2011;Berggoetz et al 2014). This suggest that the preferential host of T. velifera A may be antelope and an antelope tick vector.…”
Section: The T Velifera Cladementioning
confidence: 99%
“…More sequences were found for T. mutans-like 1/2/3 compared to T. mutans and T. mutans MSD, suggesting that these latter genotypes generally occur at lower parasitemia in buffalo than buffalo specific genotypes. This is of interest since, RLB based studies indicated a high prevalence of T. mutans in buffalo (Oura et al 2011;Chaisi et al 2011;Pienaar et al 2014), but this has probably been confounded by the non-specificity of the T. mutans probe that also detect T.…”
Section: Prevalence and Relative Parasitemia Trendsmentioning
confidence: 99%
“…In Uganda, severe anaplasmosis, ECF, and babesiosis were reported a decade ago as causes of livestock morbidity and mortality around the Lake Victoria basin (29). More recently, high prevalences of diverse Theileria, Anaplasma , and Ehrlichia species have been identified among wildlife hosts in Lake Mburo National Park, Uganda (30) and Laikipia County, Kenya (31), and among ticks sampled in the Shimba Hills National Reserve, Kenya (32). …”
Section: Introductionmentioning
confidence: 99%